COMPARATIVE STUDIES REGARDING THE USE OF RECYCLED PVC IN FINITE PRODUCTS - PETRI, Zosin Sergiu; RISTOIU, Dumitru; BELDEAN-GALEA, Mihail Simion; MIHĂIESCU, Radu (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
The PVC wastes generated by post-industrial and post-consume activity creates serious problems regarding their wastes management. In the last years, the concept of reusing these wastes in other finite products became very attractive due to some advantages such as: eliminate the problems of their storage, decrease the price of the products in which these wastes are enclosed, and protect the environment against pollution. This paper presents some comparative studies regarding the use of recycled PVC in finite products such as obtaining PVC multilayer pipes. The quality and performances of the new products were compared with products in which only virgin PVC is used. The results showed that the quality of the finite products which contained recycled PVC is comparable with those of virgin PVC. Thus rigidity, flexibility, dimensional variation and shock resistance are similar or even superior if we use recycled PVC as raw material. The conclusion is that recycled PVC can be successful reused for obtaining PVC multilayer pipes being suitable to use in a percentage of 30-50%. Moreover, the economical benefices of this method are considerable.